Modular verification of collaboration-based software designs. - Fisler, Kathi (Software engineering notes.)
Most existing modular model checking techniques betray their hardware roots: they assume that modules compose in parallel. In contrast, collaboration-based software designs, which have proven very successful in several domains, are sequential in the simplest case. Most interesting collaboration-based designs are really quasi-sequential compositions of parallel compositions. These designs demand and inspire new verification techniques. This paper presents algorithms that exploit the software's modular decomposition to verify collaboration-based designs. Our technique can verify most properties locally in the collaborations; we also characterize when a global state space construction is unavoidable. We have validated our proposal by testing it on several designs.